北极地区碳循环研究意义和展望 - 陈立奇; 高众勇; 杨绪林; 詹力杨 (2004)
全球变暖引发了北极地区的快速变化。北极地区苔原冻土带退化、海冰面积退缩和厚度变薄将使北极生态系发生重要变化 ,因而引起碳的生物地球化学循环过程变异。为精确评估北极地区对人为大气CO2 的吸收通量 ,围绕北极苔原、边缘海和极区海域的碳循环研究引起了重视。调查表明 ,北冰洋和亚北冰洋海冰区是海洋吸收大气CO2 的重要汇区 ,北冰洋具有吸收大气CO2 约 1×GtC/a的能力 ,北冰洋夏季冰缘区的长光照和高生产力促进了对大气CO2 的吸收能力 ,北冰洋深水环流和通风作用也有利于表层碳向深水转移。最近有些调查表明 ,如温度继续升高 ,北极苔原有可能从碳汇转变成大气碳源。国际上正加强北极地区碳循环研究的规划和计划 ,企图通过改进现场调查观测手段以及研究方法 ,来定量研究和模式预测变化中北极地区的碳汇潜力及其对地球气候的影响。 The Global warming has been causing rapid changes in the Arctic region. Since last decades, more and more evidences have shown that tundra degraded, sea ice's coverage decreased, center Arctic sea ice's thickness reduced, etc. The changes above in the Arctic would influence carbon biogeochemistry. Therefore, an intention has been paid to investigate carbon cycles on tundra, marginal seas and the Arctic Ocean in the Arctic in order to precisely evaluate uptake fluxes of the anthropogenic atmospheric CO 2. Results have suggested that significant regions for ocean's absorption of the atmospheric CO 2 in the Arctic Ocean and subarctic waters. It was estimated that a potential increase uptake CO 2 capacity would be about 1×Gt C a -1 for the Arctic Ocean due to a long solar radiation and high biological production in the marginal regions in summer would drive a biological pump to effectively absorb the atmospheric CO 2. The deep sea circulation and ventilation would also benefit to transfer CO 2 from surface water to deep sea water. Recent investigations have indicated that a possibility might happen that a sink in the tundra regions in the Arctic would be changed to a source of the atmospheric CO 2 when the global temperature to be increasing. An effort has been practiced to enhance the plan and implementation of carbon cycle researches in the Arctic including improving fields observing methods and modeling for forecasting variations and uptake capacity of CO 2 in the Arctic as well as feedback to the global climate. 中国首次北极科学考察和第二次北极科学考察资助;; 国家自然科学基金 ( 4 0 2 760 0 1 )资助